Intriguing 3D micro-flower structure of Co1.11Te2 deposited on Te nanosheets showing an efficient bifunctional electrocatalytic property for overall water splitting. (10th April 2023) - Wang, Guanglan; Hua, Chengye; Chen, Weixin; Fan, Heliang; Feng, Peizhong; Zhu, Yabo
Abstract: The development of efficient and low-cost bifunctional catalysts for electrochemical water splitting is important for future sustainable hydrogen energy deployment. In this paper, a series of composition-controlled hybrid catalysts (Co1.11 Te2 /Te) were successfully constructed by introducing different proportions of Co source into the precursor solutions during the hydrothermal synthesis of Te nanosheets(Te NSs). The experimental results show that the content of Co 3+ active species in the hybrid materials can be adjusted by controlling the molar ratio of Co to Te, thereby significantly improving the electrocatalytic performance of the samples. Benefiting from the highest content of Co 3+, the large specific surface area, and the great charge transfer ability, the Te-Co-3 electrode exhibited the best catalytic activity and durability among all samples. The hydrogen evolution reaction(HER) and oxygen evolution reaction(OER) overpotentials of the electrode were only 135 and 261 mV, respectively, to drive a current density of 10 mA cm −2 in an alkaline environment (1 M KOH). Furthermore, it required only a cell potential of 1.56 V to achieve overall water splitting at 10 mA cm −2 . This work should be useful for the design and preparation of non-noble metal bifunctional catalysts.